A Colonial Intellectual's Project and Its Limitations in Transcending ‘Nation’-Focusing on Jang Hyuk-ju's Novels The Man Who Was Divided (1933) and Pilgrimage (1943) - Choi, Seok-Yeol (International Journal of Korean Humanities and Social Sciences, 2025)
This article is to illuminate the compositional principle and meaning of his novel, which could not be revealed due to the recognition of being a 'pro-Japanese' writer, through re-reading of Jang Hyuk-ju's novel published during the colonial period. In other words, it is to try to find out what topics he consistently pursued through writing novels and how he chose to create texts for this purpose. In a situation where even individual desires were suppressed and controlled, colonial intellectuals participated in the production of the discourse while expanding the universalist or inclusive dimension of Japanese nationalism as much as possible to secure their own stable position. The same is true of Jang Hyuk-ju, who had creative activities in the imperial-colonial system. Therefore, if the literary artists' actions were born out of an active and independent attitude in the antagonism against the imperial Japanese system, what should be noted is their internal logic formed to cope with this situation. In other words, the important thing in interpreting those who are interpreted and judged by the standards of pro-Japanese/anti-Japanese, cooperation/resistance at the end of the colonial period is not to pay attention to the result of the action, but to the ‘process’ of how to deal with the period. This is to carefully examine the question of why ‘pro-Japanese literature’ committed such ‘blindness’ if it was ‘historical blindness’, or whether they (authors with pro-Japanese literature) thought that ‘pro-Japanese’ was not ‘historical blindness’, or if not, what ‘historical purpose’ is at work there.